Assessing COVID-19 Pandemic-Era Vaccine Uptake and Adherence to Prevention Measures: A Comparative Analysis Among Men and Women Using Lot Quality Assurance Sampling in Central Uganda - Anguyo RO; Mukama SC; Tasaga C; Bindeeba DS; Senyimba C; Ezajobo S; Nakawesi JS; Mugisa A; Nakubulwa SK; Namitala II E; Aniku G; Katongole SP (Risk Management and Healthcare Policy)
Robert Onzima DDM Anguyo,1 Semei Christopher Mukama,2 Charles Tasaga,2 Dedrix Stephenson Bindeeba,2 Catherine Senyimba,2 Simons Ezajobo,2 Jane Senyondo Nakawesi,2 Andrew Mugisa,2 Susan Kiwanuka Nakubulwa,2 Eve Namitala II,3 Gilbert Aniku,4 Simon Peter Katongole5 1Department of International Public Health, Liverpool School of Tropical Medicine (LSTM), Kampala, Uganda; 2Mildmay Uganda, Naziba Hill, Lweza, Kampala, Uganda; 3RA International, Medical Department, Mogadishu Somalia, Dubai, United Arab Emirates; 4Department of Paediatrics and Child Health, Arua Regional Referral Hospital, Arua, Uganda; 5School of Public Health, Gudie University Project, Kampala, UgandaCorrespondence: Simon Peter Katongole, Email spkatongole@gmail.comAim: This study examined citizens’ knowledge and compliance with COVID-19 standard operating procedures (SOPs), vaccine acceptance and hesitancy, and factors that could influence these behaviors.Methods: The study that utilised the Lot Quality Assurance Sampling (LQAS) approach was conducted in eight districts of Central Uganda; Kiboga, Kyankwanzi, Mubende, Kasanda, Mityana, Luwero, Nakaseke, and Nakasongola districts. Each district was divided into five supervision areas (SAs). Data were collected from 19 respondents per SA, focusing on women aged 15– 49 years and men aged 15 years and above. A satisfactory performance for study indicators was determined by the LQAS decision rules.Results: There was high awareness of COVID-19, with 98.2% of women and 99.3% of men having heard of the pandemic. However, knowledge of at least four COVID-19 preventive measures was low, reported by only 45.4% of women and 48.6% of men. Adherence to social distancing measures in the previous 24 hours was modest, with 67.2% of men and 66.5% of women complying. There was a pronounced lack of hand hygiene, with only 24.8% of women and 19.0% of men frequently washing their hands or using hand sanitizer. COVID-19 vaccine uptake was relatively high for the first dose, with 83.5% of women and 83.0% of men receiving at least one dose. However, full vaccination coverage was low, at 37.5% for women and 41.5% for men. A hesitancy to get vaccinated was driven by fear of side effects, misinformation, doubts about vaccine effectiveness, long distances and queues, and beliefs that vaccines cause infertility.Conclusion: While awareness of COVID-19 was high, knowledge of preventative measures was lacking. The low vaccination rates highlight barriers to uptake. A tailored, trust-based messaging approach through community leaders was recommended to address these gaps. Inter-district and inter-SA disparities indicated the need for localized interventions.Keywords: COVID-19, vaccine, vaccination, uptake, hesitancy, standard operating procedure